Present and future of treatment complementary (adjuvant and neoadjuvant) of breast cancer - Aizen, Bernardo; Aguiar, Sergio; Silva, Celso (Cirugía del Uruguay, 1996)
The authors describe the therapeutical properties, toxicity and indications of non-surgical treatment of breast cancer (chemotherapy, hormonotherapy, radiotherapy), and based on these data make considerations on adjuvant and neoadjuvant treatment of this conditions. Final/y, the analyze advances in genetical research and chemoprevention, speculating on its impact on the global prognosis of breast cancer in the medium rate